2019
DOI: 10.2142/biophysico.16.0_41
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron-radiation vacuum-ultraviolet circular dichroism spectroscopy in structural biology: an overview

Abstract: Circular dichroism spectroscopy is widely used for analyzing the structures of chiral molecules, including biomolecules. Vacuum-ultraviolet circular dichroism (VUVCD) spectroscopy using synchrotron radiation can extend the short-wavelength limit into the vacuum-ultraviolet region (down to ~160 nm) to provide detailed and new information about the structures of biomolecules in combination with theoretical analysis and bioinformatics. The VUVCD spectra of saccharides can detect the high-energy transitions of chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 156 publications
(213 reference statements)
0
4
0
Order By: Relevance
“…It is significant that positive and negative peaks at the CD spectra directly correlate with the usual absorption peaks [48]. The exceptionally large positive band at about 185 nm occurs at the vacuum UV CD spectra of the right-handed double-and single-stranded RNAs [48], [49]. RNA usually meets as a single-stranded molecule with a right-handed helical conformation.…”
Section: Far-uv Absorbance Peak Of Dna and Rnamentioning
confidence: 99%
See 1 more Smart Citation
“…It is significant that positive and negative peaks at the CD spectra directly correlate with the usual absorption peaks [48]. The exceptionally large positive band at about 185 nm occurs at the vacuum UV CD spectra of the right-handed double-and single-stranded RNAs [48], [49]. RNA usually meets as a single-stranded molecule with a right-handed helical conformation.…”
Section: Far-uv Absorbance Peak Of Dna and Rnamentioning
confidence: 99%
“…The research studies analysis shows that the far-UV range radiation is also a specific one for DNA and RNA. It was found that genome structures have an absorption peak in the range of 185-186 nm [48][49][50][51][52]. Vacuum-UV circular dichroism (CD) spectroscopy was mainly used for the measurements.…”
Section: Far-uv Absorbance Peak Of Dna and Rnamentioning
confidence: 99%
“…Detecting these CD signals in the far-UV-visible region poses a challenge for commercial instruments. 53,54 The CD spectra in Fig. S6 † display absorption maxima at 210-230 nm for different pairs of pure amino acids, attributed to the amino acids π-π* transition with groups aromatic in nature.…”
Section: Sensing and Recognition Of D/l-amino Acids Using Circular Di...mentioning
confidence: 99%
“…In recent years the availability of high intensity synchrotron radiation light sources has led to the creation of synchrotron radiation circular dichroism (SRCD) beamlines. These have enabled examination of a wider range of sample types, using smaller amounts of precious materials, and exploration of a broader spectral range (including not only UV data but also extending into VUV wavelengths, which have increased the information content of the spectral data obtained) (Wallace and Janes, 2009; Gekko, 2019). As CD and SRCD measurements can be obtained in solution over a range of temperatures and protein concentrations, and under dynamic conditions, both with and without substrate or modulator molecules present, they are now providing valuable complementary information (albeit at lower resolution) to other structure techniques such as X‐ray crystallography, cryo‐electron microscopy, NMR spectroscopy, and solution scattering.…”
Section: Introductionmentioning
confidence: 99%